Anabolic and lipolytic actions of beta2‐agonists in humans and antidoping challenges. Issue 5 (20th February 2020) - Hostrup, Morten; Jacobson, Glenn A.; Jessen, Søren; Lemminger, Anders Krogh
Abstract: Inhaled beta2 ‐adrenoceptor agonists (beta2 ‐agonists) are among the most used substances in competitive sports. The 2020 Prohibited List issued by the World Anti‐Doping Agency restricts use of all selective and non‐selective beta2 ‐agonists in‐ and out‐ of competition with few exemptions. Formoterol, salbutamol, and salmeterol are allowed by inhalation within defined dosing limits. These restrictions are in place because supratherapeutic use of beta2 ‐agonist has the potential to be anabolic and to enhance performance, as well as due to potential side effects. Despite substantial documentation that beta2 ‐agonists exert anabolic and lipolytic actions, these actions are not widely recognized. Furthermore, a common misconception is that the inhaled route does not exert these effects. However, given the high relative systemic bioavailability via the inhaled route, inhalation at high doses can also exert anabolic and lipolytic actions. In this review, we highlight the anabolic and lipolytic actions beta2 ‐agonists can exert, regardless of the type of beta2 ‐agonist and the route of administration. The doses needed to provide such effects are also associated with adverse effects and would in most cases be detected in routine doping control. Notwithstanding, the beta2 ‐agonist regulations are associated with some challenges and given their ability to induce muscle growth and to enhance performance, it is important to continue developing effective detection strategies to prevent potential misuse of beta2 ‐agonists while allowing treatment of asthmatic subjects without causing adverse side effects or ergogenic actions.